2015
DOI: 10.18632/oncotarget.3891
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of halofuginone in a preclinical model of osteosarcoma: inhibition of tumor growth and lung metastases

Abstract: Osteosarcoma is the main malignant primary bone tumor in children and adolescents for whom the prognosis remains poor, especially when metastases are present at diagnosis. Because we recently demonstrated that TGF-β/Smad cascade plays a crucial role in osteosarcoma metastatic progression, we investigated the effect of halofuginone, identified as an inhibitor of the TGF-β/Smad3 cascade, on osteosarcoma progression. A preclinical model of osteosarcoma was used to evaluate the impact of halofuginone on tumor grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Interestingly, Hippo/YAP signaling was seen to interact with TGF-β signaling pathway in mesothelial or skin epithelial cells at transcriptional level [96,97] ( Figure 3). Since several studies demonstrated the crucial role of the TGF-β to promote OS tumor progression [98][99][100], we could formulate the hypothesis that unless it has the ability to interact with TEAD, YAP would be able to interact with the TGF-β signaling pathway to promote OS development specifically metastatic process. Crosstalk between YAP signaling pathway and both TEAD and TGF-β pathways.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Interestingly, Hippo/YAP signaling was seen to interact with TGF-β signaling pathway in mesothelial or skin epithelial cells at transcriptional level [96,97] ( Figure 3). Since several studies demonstrated the crucial role of the TGF-β to promote OS tumor progression [98][99][100], we could formulate the hypothesis that unless it has the ability to interact with TEAD, YAP would be able to interact with the TGF-β signaling pathway to promote OS development specifically metastatic process. Crosstalk between YAP signaling pathway and both TEAD and TGF-β pathways.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Although the invasion of tumor cells is a general characteristic in carcinogenesis, metastasis to the lung is one of the main characteristics in patients with OS and one of the major causes of mortality [54,55], so this event is a hallmark for this sarcoma. Pathogenic events, including cellular detachment from primary tumors, matrix remodeling and invasion from tumor cells, angiogenesis, vascular dissemination, and proliferation at new sites, are involved in tumor metastasis [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, using molecular (over-expression of the inhibitor Smad, Smad7) and pharmacological (SD-208 and/or halofuginone) approaches, we clearly demonstrated that TGF-βs affect osteosarcoma tumor growth and lung metastatic development [38,89]. Of note, SD-208 is a chemical inhibitor of TβRI, and halofuginone is an alkaloid known for its inhibitory properties on the TGF-β signaling pathway [90].…”
Section: Tgf-β and Osteosarcomamentioning
confidence: 99%
“…In addition, we demonstrated that blocking the TGF-β cascade in tumor cells inhibits the expression of TGF-β target genes, such as IL-11, CXCR4, and osteopontin, known to enhance bone metastasis formation from breast cancer cells or melanoma [92,93,94,95]. Of note, in contrast to Smad7, the effects of halofuginone appear to be mainly due to its pro-apoptotic properties in osteosarcoma, regardless of its ability to inhibit the TGF-β signaling pathway [89]. The role of the non-canonical TGF-β signaling pathway in osteosarcoma progression is poorly documented.…”
Section: Tgf-β and Osteosarcomamentioning
confidence: 99%